Sensitivity of simulations of Plio–Pleistocene climate with the CLIMBER-2 Earth System Model to details of the global carbon cycle - Judit Carrillo; Michael E. Mann; Irina Marinov; Shannon A. Christiansen; Matteo Willeit; Andrey Ganopolski (Proceedings of the National Academy of Sciences, 2025)
The Earth system model CLIMBER-2 has been used in past work to successfully reproduce the glacial/interglacial cycles of the Plio–Pleistocene and the Mid-Pleistocene Transition (MPT) from predominantly 40 to 100 ky timescale oscillatory behavior as a function of declining volcanic outgassing and regolith removal. In this study, we further examine the sensitivity of this previous work to varying prescribed levels of volcanic outgassing and regolith extent and the long-term dynamics of the global carbon cycle, affecting the exchange and partitioning of carbon between different Earth system reservoirs and therefore global atmospheric CO 2 concentrations. As volcanic outgassing decreases, CO 2 and land carbon storage decrease, while ocean carbon storage, including CaCO 3 sediment, increases. At volcanic outgassing levels below a threshold value of roughly 5.7 Tmol C yr −1 , sea level decreases due to land ice formation, leading to increased carbon accumulation in the ocean and decreased carbon in the CaCO 3 sediment reservoir. Our previous finding of strong hysteresis and path dependence in the glacial/interglacial alternation history [J. Carrillo et al. , Proc. Natl. Acad. Sci. 121, e2322926121 (2024)] appears to be a tenuous climate feature, dependent on the precise representation of carbon cycle processes and, specifically, the numerical precision used in the calculation of certain key state variables in the model’s carbon cycle.